ANÁLISIS DE LA ACUMULACIÓN PROCESAL EN EL CÓDIGO PROCESAL CIVIL PERUANO - Vilela Carbajal, Karla (Revista de Derecho, 2022)
The paper analyzed main problems presented by the regulation of the joinder of claims and joinder of process in the Peruvian Civil Procedural Code of 1993, putting in evidence how its equivocal treatment has led to that in judicial practice to reach solutions irrational and incompatible with the principle of effectiveness of the jurisdictional protection.
Keywords: civil procedure; joinder of claims; joinder of actions; joinder of process; procedural economy